The Influence of Umrah Brand Equity Toward Customers Value, Trust, and Commitment - Aisyah Rahmawati; Asep Mulyana; Lut Mafrudoh; Ratna Suminar (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study examines the influence of Umrah brand equity on customer value, trust, and commitment toward Umrah travel agencies in DKI Jakarta. Using a quantitative approach, data were collected through an online survey of 370 pilgrims who had performed Umrah before the COVID-19 pandemic. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results show that brand equity has a positive and significant effect on customer value, trust, and commitment. Customer value and trust also positively affect pilgrims’ commitment, with customer value mediating the relationship between brand equity and commitment, while trust does not. These findings indicate that perceived value plays a stronger role than trust in enhancing pilgrims’ loyalty and long-term engagement with Umrah service providers. Theoretically, this research contributes to the understanding of brand equity within faith-based service contexts, which remain underexplored in marketing studies. Practically, Umrah travel organizers should strengthen their brand equity by improving service quality, maintaining transparency, and building a credible and consistent brand image to enhance customer value, trust, and loyalty.